A carbon nanotube/pyrrolidonecarboxylic acid zinc sponge for programmed management of diabetic wounds: Hemostatic, antibacterial, anti-inflammatory, and healing properties - Chenwei Wu; Bo Liu; Qiulan Wen; Qiliang Zhai (Materials Today Bio)
Wound healing in patients with diabetes is challenging because of chronic inflammation, inadequate vascularization, and susceptibility to infection. Current wound dressings often target specific stages of healing and lack comprehensive therapeutic approaches. This study introduces a novel approach using a photodetachable sponge scaffold incorporating carbon nanotubes (CNTs), known for their high photothermal conversion efficiency, electrical conductivity, and water absorption properties. The scaffold incorporated pyrrolidonecarboxylic acid zinc (PC1Z2), a compound with anti-inflammatory and moisturizing properties, which was cross-linked within a network of CNTs and a decellularized dermal matrix. The resulting shape-memory sponge scaffold actively interfaces with endogenous electric fields, facilitating electrical signal transmission to skin cells and accelerating tissue repair. Upon exposure to near-infrared (NIR) light, the PC1Z2 scaffold enhanced antibacterial efficacy (98 %) through photothermal conversion, promoting tissue metabolism at the wound site. Notably, the scaffold absorbed wound exudates and gradually released Zn2+, effectively reducing chronic inflammation in the mice. In a diabetic rat wound model, the PC1Z2 scaffold absorbed exudates, reduced inflammation, and accelerated granulation tissue formation, wound angiogenesis, and re-epithelialization. This innovative PC1Z2 sponge dressing shows promise for enhancing the healing of diabetic wounds.